STICKY COST BEHAVIOR OF INDONESIA STOCK EXCHANGE MANUFACTURING COMPANIES - Magdalena Nany; Kristyana Dananti; Priskilla Oktavia; Sundari Sundari (International Journal of Social Science, 2023)
When activity levels fluctuate, sticky costs tend to increase rather than decrease. The testing of a sticky cost model is used in this study to illustrate the behavior of sticky costs on the selling expenditures, general and administrative costs, and product costs that are incurred by manufacturing firms. This study makes use of secondary data collected from 164 industrial companies that were listed on the Indonesia Stock Exchange between 2018 and 2019. Multiple regression evaluated data. According to this study, selling expenses, administrative and general expenditures, as well as the cost of things sold, are all considered sticky costs. This finding confirms all previous forecasts